2012
DOI: 10.1177/0894439312465254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of E-Mailed Versus Mailed Invitations and Incentives on Response Rates, Data Quality, and Costs in a Web Survey of University Faculty

Abstract: While a large literature indicates that using a mixed-mode approach to notify or contact potential respondents can be effective in increasing response rates, surprisingly little research examines the impact the mode of invitation has on participation in a web survey. To assess the effects of invitation mode on response rates, costs, and demographic representativeness, university faculty members (N ¼ 280) were randomly assigned to experimental groups and sent a mailed invitation letter and a $2 cash incentive; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 19 publications
10
55
1
5
Order By: Relevance
“…Still, a response of 31% means that care should be taken when generalizing the findings to the whole student population. It is possible that the use of a web‐based survey approach contributed to the moderate response rate, as electronic platforms typically yield lower overall participation rates when compared with traditional postal mail approaches, such as paper‐based surveys or face‐to‐face interviews (Dykema, Stevenson, Klein, Kim, & Day, ). Related to this is the 69% female composition of the sample, which may represent a bias for the overall estimates, as females generally report worse sleep across most parameters compared with men.…”
Section: Discussionmentioning
confidence: 99%
“…Still, a response of 31% means that care should be taken when generalizing the findings to the whole student population. It is possible that the use of a web‐based survey approach contributed to the moderate response rate, as electronic platforms typically yield lower overall participation rates when compared with traditional postal mail approaches, such as paper‐based surveys or face‐to‐face interviews (Dykema, Stevenson, Klein, Kim, & Day, ). Related to this is the 69% female composition of the sample, which may represent a bias for the overall estimates, as females generally report worse sleep across most parameters compared with men.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses of techniques for improving response rates have shown that university sponsorship, prenotification, return postage, follow‐up letters, first‐class postage, color of questionnaire, and the use of cash incentives all increase response rates in mail‐based surveys (Fox et al, 1988; Yammarino et al, 1991). In web‐based surveys, personalized communications (Cook, Heath, & Thompson, 2000; Sánchez‐Fernández, Muñoz‐Leiva, & Montoro‐Ríos, 2012), activity in online communities and the use of a plea for help (Petrovčič, Petrič, & Manfreda, 2016), cash incentives (Dykema, Jones, Piché, & Stevenson, 2013), and lotteries for tangible incentives (Heerwegh, 2006) have been shown to increase response rates. The use of humor, tailored to the voice of the audience, can also increase response rates among young adults (Rath et al, 2016).…”
mentioning
confidence: 99%
“…For example, the effectiveness of mailed prenotification may depend on the accuracy of the population's mail and/or e-mail contact information. Specifically, mailed prenotification may increase response rates for populations with less reliable e-mail addresses by ensuring that individuals are notified of the study (Dykema et al 2013) but be ineffective for populations with accurate e-mail addresses. Individual differences may also correspond to increased likelihoods of responding when mail prenotification is used.…”
Section: Analysis Analysismentioning
confidence: 99%